Myxofibrosarcoma of The Abdominal Wall at Moewardi Hospital, Surakarta: A Rare Case Report - Soewoto, Widyanti; Ismail, Erwin Aritama; Bellynda, Monica (Indonesian Journal of Cancer, 2024)
Introduction: Myxofibrosarcoma (MFS) is a fibroblast-derived sarcoma, which accounts for approximately 5–10% of all soft tissue malignant tumors. The mean age in patients with MFS is between the fifth and seventh decades. Around 77% of MFS cases occur in the upper extremities. Other areas of the body including the trunk (12%), retroperitoneum or mediastinum (8%), abdominal wall, and heart have also been reported. Case Presentation: A 57-year-old Indonesian female visited our center with complaints of a lump in the left lower abdomen for 4 months. The lump has grown rapidly in the last two months. A contrast abdominal MRI examination found a soft tissue mass on the left lumbar abdominal wall to the left iliac with a size of 15 x 11,4 x 13,4 cm and bordered by part of the left external oblique muscle and the left internal oblique muscle pushing the intestinal system medially. The biopsy of the mass revealed a high-grade myxofibrosarcoma. The patient underwent a wide excision with an elliptical incision design, with in-toto removal of the lump. The immunohistochemical result of the tumor showed high-grade myxofibrosarcoma with free margins at the incision margin. Follow-up was performed at 1 month, 6 months, and 12 months postoperatively. The patient did not receive radiotherapy. Conclusions: This report describes a rare case of MFS of the abdominal wall. Recognizing the histopathological features of MFS and applying the appropriate immunohistochemical examinations are crucial in establishing the correct diagnosis. This case provides a diagnosis and treatment experience of MFS that occurs in the abdominal wall.